Low evolutionary potential for blue-green egg colouration in a wild bird population - D’Arpa, Stefania R; Gil, Diego; Muriel, Jaime; Monclús, Raquel; Pérez-Rodríguez, Lorenzo; Martínez-Padilla, Jesús (John Wiley & Sons, 2025)
Exploring the evolutionary architecture of female sexual traits and their potential evolvability is important to understand their possible role as post-mating sexual signals. Egg colouration has been proposed to be one of these post-mating sexual signals, honestly advertising female quality in birds, especially in blue-green laying species. In this study, we used an animal model in a Bayesian framework to estimate the evolvability of multiple descriptors of blue-green egg colouration and egg size in a wild long-term monitored population of spotless starlings (Sturnus unicolor). Our results show low to moderate heritability (h2 = 0.31 - 0.44) for three egg colour descriptors (blue-green chroma, chroma and lightness) and egg size. Using the coefficient of additive genetic variance (CVA) and the evolvability (IA) as proxies of evolutionary potential of all components of this trait, we found low values of CVA for all these variables, suggesting a small evolutionary potential of these phenotypic traits, contrasting to previous results reported in another blue-green egg laying species. Our results indicate a modest raw genetic material of this trait on which sexual selection can act upon and, therefore, a small probability for these traits to respond easily to selection.